Determinan Transfer Pricing Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019 - 2023 - Amalia, Vina; Alirastra Budiantoro, Risanda (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2025)
Rapid globalization has encouraged the expansion of multinational companies and the increasing complexity of cross-border transactions. Transfer pricing is an important issue in international taxation practices, because it has the potential to be used to shift profits to countries with lower tax rates. This study aims to analyze the effect of tax burden, exchange rate, bonus mechanism, and thin capitalization on transfer pricing. The method used in this research is quantitative using secondary data. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 - 2023, totaling 231 companies. The sample was selected using purposive sampling technique and obtained data totaling 25 manufacturing companies with 89 units of analysis which became the object of observation. The analytical technique used in this research is panel data regression analysis with the help of Eviews software version 12. The results showed that the tax burden has a significant positive effect on the company's decision to practice transfer pricing. This indicates that the greater the tax burden borne by the company, the greater the possibility of the company to practice transfer pricing. Meanwhile, the exchange rate variable, bonus mechanism, and thin capitalization have no significant effect on the company's decision to practice transfer pricing. In conclusion of this study, the company management is advised to consider the decision in conducting transfer pricing practices and be more careful in conducting transfer pricing. Meanwhile, the government and tax authorities are expected to increase and tighten supervision of companies conducting related transactions in order to minimize tax avoidance practices through transfer pricing practices. Rapid globalization has encouraged the expansion of multinational companies and the increasing complexity of cross-border transactions. Transfer pricing is an important issue in international taxation practices, because it has the potential to be used to shift profits to countries with lower tax rates. This study aims to analyze the effect of tax burden, exchange rate, bonus mechanism, and thin capitalization on transfer pricing. The method used in this research is quantitative using secondary data. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 - 2023, totaling 231 companies. The sample was selected using purposive sampling technique and obtained data totaling 25 manufacturing companies with 89 units of analysis which became the object of observation. The analytical technique used in this research is panel data regression analysis with the help of Eviews software version 12. The results showed that the tax burden has a significant positive effect on the company's decision to practice transfer pricing. This indicates that the greater the tax burden borne by the company, the greater the possibility of the company to practice transfer pricing. Meanwhile, the exchange rate variable, bonus mechanism, and thin capitalization have no significant effect on the company's decision to practice transfer pricing. In conclusion of this study, the company management is advised to consider the decision in conducting transfer pricing practices and be more careful in conducting transfer pricing. Meanwhile, the government and tax authorities are expected to increase and tighten supervision of companies conducting related transactions in order to minimize tax avoidance practices through transfer pricing practices.